FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN ALAT KONTRASEPSI PADA WANITA USIA SUBUR DI PUSKESMAS JOMBANG-KOTA TANGERANG SELATAN - Huda, Andari Nurul; Widagdo, Laksmono; Widjanarko, Bagoes (Jurnal Kesehatan Masyarakat (Undip), 2016)
The high birth rate in Indonesia at this time is one of  a big problems and need the special attention in its handling to control the birth rate. One form of special attention of government in handling high birth rate that is by implementing development and family planning comprehensively. Total fertility rate in woman of fertile age 15-49 years old according to the Indonesian Demographic and Health Survey in 2012 is 2,6. Total population in South Tangerang City at 2013 as many as 1.443.403 people and includes 4 largest population in Banten. The percentage of use contraception in women fertile age is 80,56%, while for the attainment of target family planning in Jombang Health Centers South Tangerang is 99%. The purpose of this research is to analyze factors associated with the behavior of contraceptive use in women fertile age. This research uses quantitative research with cross sectional approach. The population in this research are woman fertile age who use contraceptives a number of 8512 and 95 samples were taken using incidental sampling method. Analysis of data using Chi Square test with a significance level of 0,05. The results showed that the factors associated with the behavior of the use of contraceptives is knowledge (p-value: 0,019), attitude (p-value: 0,034), the support of husband (p-value: 0,000), the role of heath personnel (p- value: 0,009). People should be more active in seeking information about contraceptives and encourage the closest people to participate in family planning programs.